Disseminated Intravascular Coagulation as a Possible Cause of Acute Coronary Stent Thrombosis: A Case Report and Literature Review. (20th December 2012) - Amer, Syed; Shafiq, Ali; Qureshi, Waqas; Muqeetadnan, Mohammed; Hassan, Syed
Abstract : Disseminated intravascular coagulation (DIC), as a cause of acute coronary stent thrombosis, has not yet been reported to our knowledge. We report a case of 64-year-old male, who presented with non-ST-segment elevation myocardial infarction (NSTEMI). Coronary angiography revealed right coronary artery (RCA) stenosis and a drug eluting stent was deployed. Fifteen hours following the intervention, the patient developed an inferior wall ST elevation myocardial infarction. Repeat cardiac catheterization showed an acute in-stent thrombosis. Following thrombectomy, another stent was placed. The patient noted to have an acute drop in platelet count following the second intervention. Two hours following repeat intervention, the patient again developed chest pain and EKG showed recurrent ST-segment elevations in leads II, III, and aVF. Prior to repeat cardiac catheterization, the patient became unresponsive and developed cardiogenic shock. The patient was resuscitated and intubated, and repeat catheterization showed complete stent thrombosis. Intracoronary tissue plasminogen activator (tPA) was given. The platelet count further dropped. Additional studies confirmed the diagnosis of DIC. No further cardiac catheterization was done at this point. The patient then later had a cardiac arrest and unfortunately cardiopulmonary resuscitation could not revive him. Amongst the etiologies of acute stent thrombosis, DIC was deemed a possible cause.